Factors associated with prolonged grief, PTSD, and anxiety-depressive distress among individuals who lost loved ones during the war in Ukraine - Leshchuk, Iryna; But, Tetiana; Zelenko, Yelyzaveta; Frankova , Iryna (Psychosomatic Medicine and General Practice, 2025)
Background. Wartime conditions are associated with heightened psychological burden, multiple losses, and disruption of social ties – all of which may contribute to the development of prolonged grief disorder (PGD), post-traumatic stress disorder (PTSD), and anxiety and depressive disorders. Aim. This study sought to identify factors associated with the severity of PGD, PTSD, anxiety, and depression symptoms in adults experiencing bereavement during the ongoing war in Ukraine. Methods. A cross-sectional online study was conducted with 194 adult participants, who completed a battery of validated questionnaires assessing grief symptoms (TGI-SR-ICD-11), PTSD (PCL-5), anxiety and depression (PHQ-4), anxious and depressive avoidance (DAAPGQ-5), maladaptive grief-related cognitions (GCQ-12), experience of loss unreality (EUS), somatic symptom severity (SSS-8), coping efficacy (SCES+), and war-related stress (WRSS). Multiple linear regression with assumption testing was used as the primary statistical method. Results and Discussion. The model accounted for 73.5% of the variance in PGD symptom severity (R² = 0.735). The strongest contributing factors were maladaptive grief-related cognitions, anxious and depressive avoidance, and lower coping efficacy. Certain aspects of loss unreality experience and subjective exhaustion also made independent contributions. Marital status was statistically significant, whereas education did not show a consistent association after controlling for other variables. The regression model for anxiety and depression symptoms was statistically significant and explained a moderate share of PHQ-4 score variance (R² = 0.328; adjusted R² = 0.242). Type III omnibus tests identified significant contributions from gender, state and social support, education level, and closeness of relationship with the deceased; cause of loss showed a borderline result. Time since loss did not reach statistical significance after adjustment. For PTSD symptom severity, the model was statistically significant and explained a moderate portion of PCL-5 variance (R² = 0.264; adjusted R² = 0.167), with closeness of relationship as the only significant predictor. Education, forced displacement, cause of loss, social support, and gender showed borderline results that did not reach statistical significance. Conclusions. This study contributes to the understanding of relationships between mental health outcomes – PGD, PTSD, anxiety, and depression – and sociodemographic, cognitive-behavioral, and war-related factors in bereaved individuals. The findings highlight the importance of targeted psychosocial interventions focusing on cognitive-behavioral factors (reducing anxious and depressive avoidance and maladaptive grief cognitions, and strengthening coping mechanisms) as well as enhancing social support. Keywords: prolonged grief disorder; complicated grief; post-traumatic stress disorder; depression; anxiety; comorbidity; risk factors; maladaptive cognitions; anxious and depressive avoidance; coping.